Diabetes and Hypertension Prevention and Control in Community Health Centers: Impact of the Affordable Care Act - Nathalie Huguet; Beverly B. Green; Annie E. Larson; Laura Moreno; Jennifer E. DeVoe (SAGE Publishing, 2023)
Access to care significantly improved following the implementation of the Patient Protection and Affordable Care Act. Since its implementation, the number of uninsured Americans has significantly decreased. Medicaid expansion played an important role in community health centers, who serve historically marginalized populations, leading to increased clinic revenue, and improved access to care. As the continuous Medicaid enrollment provision established during the pandemic ended, and states have to make decisions about their program eligibility, exploring the impact of Medicaid expansion on the detection, and management of hypertension and diabetes could inform these decisions. We summarized the effect of Medicaid expansion on community health centers and their patients specific to hypertension and diabetes from existing literature. These studies suggest the beneficial impact of the Affordable Care Act and acquiring insurance on diabetes and hypertension disease detection, treatment, and control for patients receiving care in community health centers. Overall, these studies suggest the clear importance of health insurance coverage, and notably insurance stability, on diabetes and hypertension control.